New insights into geological setting of the summit area of mount Etna volcano (Italy) inferred from 2D gravity data modelling - Pánisová, Jaroslava; Greco, Filippo; Carbone, Daniele; Branca, Stefano Felice; Vajda, Peter (Frontiers in Earth Science, 2023)
Gravimetric observations were carried out in 2015, to image the uppermost portion of the volcanic plumbing system of Mt. Etna (Italy). Gravity measurements were performed using two relative gravimeters, along a profile that crosses the summit craters area (elevations between 2820 and 3280 m a.s.l.). Accurate positioning of the gravity observation points was determined through GPS measurements. After applying elevation and terrain corrections, the reduced gravity data were used to build a 2D density model of the uppermost part of the volcano edifice. This model was constrained using to-date knowledge of the structural setting of the area and the available volcanological data. We highlighted the presence of low-density material below the summit craters, down to the depth of about 2.1 kilometres, interpreted as highly altered, fumarolized and structurally weakened material. It is also likely that the close presence of the conduits feeding the summit craters of the volcano contributes to the gravity low in the SW half of the measurement profile. Conversely, the gravity low observed at the northern edge of the profile could reflect the high concentration of faults and eruptive fissures in the Pizzi Deneri area, in correspondence of the Ellittico caldera rim.